A Postscript to Panel Discussion of Gianni Nebbiosi's "The Smell of Paper: On the Usefulness of Musical Thought in Psychoanalytic Practice". Issue 1 (2nd January 2016) - Cooper, Steven H.
Abstract : Gianni Nebbiosi's paper, "The Smell of Paper: On the Usefulness of Musical Thought in Psychoanalytic Practice, " explores many levels of the analyst's clinical sensibility. These include the finding of a patient in the mind of the psychoanalyst, the discovery of new points of creative inflexion in developing metaphors with a patient who is frightened of symbolic meaning, the use of countertransference analysis to explore the analyst's points of resistance to helping his or her patient, and the development of a creative shared frame of reference between patient and analyst that emerges from the patient's unconscious life.